Pemanfaatan Metode TOPSIS dalam Menentukan Rekomendasi Laptop Unggulan di Marketplace Tokopedia - Pratiwi Susanti; Saifulloh Saifulloh; Alim Citra Aria Bima; Muh Nur Lutfi Aziz; Latjuba Sofyana STT (Lembaga Pengembangan Kinerja Dosen, 2025)
The increasing public demand for laptop devices, particularly through marketplace platforms like Tokopedia, results in challenges when selecting a laptop that meets users' needs and preferences. Explore the key laptop specifications that are most important to consumers, such as battery life, RAM, and storage options. Discuss current market trends in laptop sales, including the most popular brands and models among users on platforms like Tokopedia. Highlight the importance of user reviews and testimonials in guiding potential buyers toward their ideal laptop choice. Provide tips for effective comparison shopping on marketplace platforms to help users narrow down their options. Analyze how different consumer preferences (e.g., gaming vs. productivity) influence the types of laptops that are in demand. This study aims to build a Decision Support System (DSS) for selecting the best laptop using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method. The study was conducted by identifying the main criteria, such as price, RAM, CPU, memory, and dimensions of the laptop, which were then used in the TOPSIS calculation process to determine the best alternative from 15 laptop choices. The results of the study show that the TOPSIS method is able to provide accurate and swift recommendations in choosing a laptop based on user preferences. We implement the system as a website, enabling users to input their preferences and receive automatic laptop recommendations. We expect this study to assist users in making laptop purchasing decisions more effectively and efficiently